Language Change on Social Media - Celine Christina Luhulima; Endar Rachmawaty Linuwih; Duncan Reinhart Hutagaol; Nofiyanti Nofiyanti (International Journal of English and Applied Linguistics (IJEAL), 2024)
Language change is the permanent alteration of a language's features and usage over time, affecting various aspects such as sound, vocabulary, meaning, and syntax. This research explores language change in the context of social media, specifically focusing on YouTube podcasts. The main goal is to understand how certain parts of speech, like pronouns, verbs, and adjectives, transform into specialized terms unique to the social media environment. The study aims to answer the question: "How do words evolve into special terms in the context of social media use, particularly in YouTube podcasts?”. To comprehensively understand this linguistic phenomenon, a descriptive qualitative approach will analyze data from the dynamic realm of social media, focusing on YouTube, particularly YouTube podcasts. The sample set includes content like "Volix Media - EPISODE PENUH SENSOR SAKING BANYAK "RUMPI"NYA | VINIAR : Talk Show." Insights from relevant website articles will also contribute to the analysis. Forty one words from YouTube podcasts were selected and translated into English. The findings suggest language changes evolve with time and societal shifts. Older times featured distinctive words or abbreviations limited to specific communities, whereas today, global trends and social developments contribute to new language variations and the emergence of new terms through language mixing